The Gulf Ecosystem Health and Sustainability - Price, Andrew, 1950-; Munawar, M.; Khan, N. Y. (Nuzrat Yar) (Ecovision world monograph series., 2018)
The Persian Gulf's marine environment has suffered from a variety of perturbations, most resulting directly or indirectly from the extraction of oil and subsequent development projects--drilling, refining, dredging, and landfilling, as well as from worldwide maritime transportation. In addition, the environment and its people have suffered from the Iran-Iraq war in the early 1980s and from Iraq's invasion of Kuwait in 1990. Since then the countries of the Gulf, in collaboration with regional and international organizations, have initiated extensive measures for the protection and conservation of the Gulf. One such initiative was the decision by the Kuwait Institute for Scientific Research to publish a state-of-the-art monograph to address and document the complex subject of the health and sustainability of the gulf ecosystem.